Exploring the bacterial assemblages along the human nasal passage. (July 2016) - Wos‐Oxley, Melissa L.; Chaves‐Moreno, Diego; Jáuregui, Ruy; Oxley, Andrew P. A.; Kaspar, Ursula; Plumeier, Iris; Kahl, Silke; Rudack, Claudia; Becker, Karsten; Pieper, Dietmar H.
Summary: The human nasal passage, from the anterior nares through the nasal vestibule to the nasal cavities, is an important habitat for opportunistic pathogens and commensals alike. This work sampled four different anatomical regions within the human nasal passage across a large cohort of individuals ( n  = 79) comprising individuals suffering from chronic nasal inflammation clinically known as chronic rhinosinusitis (CRS) and individuals not suffering from inflammation (CRS‐free). While individuals had their own unique bacterial fingerprint that was consistent across the anatomical regions, these bacterial fingerprints formed into distinct delineated groups comprising core bacterial members, which were consistent across all four swabbed anatomical regions irrespective of health status. The most significant observed pattern was the difference between the global bacterial profiles of swabbed and tissue biopsy samples from the same individuals, being also consistent across different anatomical regions. Importantly, no statistically significant differences could be observed concerning the global bacterial communities, any of the bacterial species or the range of diversity indices used to compare between CRS and CRS‐free individuals, and between two CRS phenotypes (without nasal polyps and with nasal polyps). Thus, the role of bacteria in the pathogenesis of sinusitis remains uncertain.